Effects of suspension exercise training in the treatment of lumbar disk herniation: a systematic review and meta-analysis - Liu, Yu’ang; Huang, Silang; Zhang, Xinxin; Liao, Huangying; Liu, Weiguo; Zhang, Zhi (Frontiers in Neurology, 2024)
ObjectiveThe study aimed to systematically evaluate the efficacy of suspension exercise training (SET) in the treatment of lumbar intervertebral disk herniation and provide a scientific basis for clinical treatment.MethodsDatabases such as CNKI, Chinese Wanfang, PubMed, Cochrane, the Web of Science, and Embase were searched up to June 2024. A quality assessment was performed using the Cochrane Collaboration’s risk-of-bias guidelines, and a meta-analysis was conducted using RevMan 5.4 and Stata 17.0.ResultsA total of 11 studies involving 943 patients were included. Suspension exercise training significantly improved the lumbar disk herniation (LDH) visual analog scale (VAS) score (mean difference (MD) = −0.96; 95% confidence interval (CI), −1.10 to-0.82; p < 0.00001, I2 = 23%), the Japanese Orthopedic Association (JOA) score (MD = 3.29, 95% CI, 1.67 to 4.90; p < 0.0001, I2 = 92%), and the Oswestry Disability Index (ODI) score (MD = −5.41, 95% CI, −7.41 to −3.40; p < 0.00001, I2 = 86%). Subgroup analysis of the JOA score showed better efficacy with suspension exercise training combined with traditional Chinese medicine (TCM) (MD = 4.29, 95% CI, 2.73 to 5.86; p < 0.00001, I2 = 80%) compared to suspension exercise training combined with non-TCM (MD = 0.96, 95% CI, 0.49 to 1.43; p < 0.0001, I2 = 0%).ConclusionSuspension exercise training significantly improved the VAS score, JOA score, and ODI score of the patients with lumbar disk herniation; however, there was a high degree of heterogeneity in the JOA score and ODI score. Further validation is needed in the future for different populations with lumbar disk herniation, the specific locations of its occurrence, and the combined modality of suspension exercise training.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024554074.